Mortalité et croissance de l'huître creuse C. gigas dans le bassin de Marennes Oléron. Résultats obtenus sur le site atelier de Ronce-Perquis en 1997-1999 - Soletchnik, Patrick; Le Moine, Olivier; Faury, Nicole; Razet, Daniel; Geairon, Philippe; Robert, Stephane; Goulletquer, Philippe; Taillade, Sylvie (2000)
The 1999 monitoring of the C. gigas mortality rates showed a 32 to 40% loss for the on-bottom rearings located on the Ronce-Perquis oyster bank. In 1997, the averaged mortality rate varied between 23 and 29% without significant site effect. These mortality rates were ranging from 17 to 32% in 1998 with significant limited mortality rate on site 4 (17%). However, those rates were underestimated by 7 to 8%, based on our 1999 study, Actually, the spatial distribution for these rates on 2 experimental sites divided into 25 subunits demonstrated a large variability ranging from 17-37% and 22-56% for sites 1 and 2, respectively. In spite this large variability, the mortality rates results were larger on the muddy bottom site. In contrast to site 1, the oysters deployed on site 2 showed a non-random mortality rate distribution with a 10% greater rate on the eastern side of the lease. This study demonstrated the likely bias induced by the traditional sampling strategy to estimate mortality rates on on-bottom oyster cultures. The loss due to spatial dispersion was estimated to reach 10 to 15%. A significant improvment in estimating mortality rates was obtained by the 1999 methodology. The mortality rate at the study completion can be divided into two parts: 1) an initial rate resulting from zootechnical practices and the oyster deployment, and 2) the rearing mortality rate function of the environmental and on-going rearing conditions. This initial mortality rate can reach greater values than the rearing mortality rate, as described in 1999. Initial mortality rates reached 3, 7 and 21% in 1997, 1998, and 1999 respectively. This also demonstrated the critical effect of the initial oyster physiological condition, and therefore the oyster batches characteristics in explaining mortality rates. The overall growth performance in terms of shell and meat weight gains was significantly lower for on bottom rearing conditions compared to off bottom culture. The Eastern experimental site located at a 75% immersion time showed ...